Systematic studies to produce heavy above-target nuclides in multinucleon transfer reactions - H.M. Devaraja; A.V. Yeremin; M.L. Chelnokov; V.I. Chepigin; S. Heinz; A.V. Isaev; I.N. Izosimov; Sh.A. Kalandarov; A.V. Karpov; D.E. Katrasev; A.A. Kuznetsova; O.N. Malyshev; et al. (Physics Letters B, 2025)
We present studies of multinucleon transfer reactions in collisions of 48Ca+208Pb, 50Ti+208Pb, and 40Ar+209Bi which lead to the population of nuclei with proton numbers greater than the target proton number. The target-like reaction products were separated in flight using the velocity filter SHELS of the Flerov Laboratory for Nuclear Reactions (FLNR), Dubna. Our goal was to examine transfer reactions for producing new heavy and superheavy nuclei and to assess the applicability of velocity filters for their investigation. We observed and studied about 40 different nuclides, resulting from the transfer of up to eight protons from the projectile to the target and moving in forward direction relative to the beam axis. We present cross-section systematics for isotopes of elements Z = (83 – 91) measured in our experiment and compare them with available data from transfer reactions with actinide targets which lead to isotopes up to Z = 103.